The Load Alternation: Semantic Shifts and Implicit Arguments - Lumsden, John (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1994)
ABSTRACTThis study argues that verbal expressions like to load, to pack, to pile, etc. are composed of specific substantive concepts and general predicate concepts. All surface expressions involve a derivation that combines these elements. Substantive concepts may also appear in nominal expressions (e.g. a load, a pack, a pile, etc.). The verbal expressions allow an alternate realization of their argument structure because the interpretation of the substantive concept undergoes a semantic shift so that it combines differently with the pertinent predicate concepts. In one realization, the substantive concept is an implicit theme argument; in the other, it is an implicit location.